2018
DOI: 10.15562/jdmfs.v3i2.736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage temperature on vickers microhardness of resin composite

Abstract: The purpose of this study is to evaluate the effect of three storage temperatures on microhardness of high-and low-viscosity bulk-fill materials and compare them with conventional resin-based composite materials. Material and Methods: Six composite resin-based materials were used in this study (TN, TNB, TNF, FZ250, FB, and FBF), samples were subdivided into three groups based on the pre-curing storage temperature (5°C, 23°C, 37°C). Light polymerization for each material was performed based on the manufacturer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Temperatures factor play an important role in the polymerization process, which alter the mechanical and physical properties of composite resin, composite is a viscoelastic material, which responds to an increase or decrease in the external temperature. (4) Dentists store composite resins in refrigerators to prolong their shelf lives usually at temperatures ranging from 2°Cto 5°C as recommended by the manufactures (5) . Darnoch et al (2006) reported that the degree of polymerization is decreased at 3°C and increased at a 60°C (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures factor play an important role in the polymerization process, which alter the mechanical and physical properties of composite resin, composite is a viscoelastic material, which responds to an increase or decrease in the external temperature. (4) Dentists store composite resins in refrigerators to prolong their shelf lives usually at temperatures ranging from 2°Cto 5°C as recommended by the manufactures (5) . Darnoch et al (2006) reported that the degree of polymerization is decreased at 3°C and increased at a 60°C (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the clinical indication, the materials designated to the posterior region showed greater potential to increase hardness when stored at room temperature (Chi-square Test -p=0.047). Hardness tests data for a specific material provide information about its wear, polish ability and abrasive effect on antagonist teeth 31 . The surface hardness of a composite resin is influenced by resin matrix, filler particle shape, distribution, size and density.…”
Section: Discussionmentioning
confidence: 99%